2012
DOI: 10.1002/ejoc.201200134
|View full text |Cite|
|
Sign up to set email alerts
|

Concise Synthesis of Norrisolide

Abstract: The marine natural product norrisolide has been synthesized in a convergent manner with a longest linear sequence of 14 steps. The hydrindane portion of the molecules is prepared through conjugate addition of a functionalized allyl group into cyclopentenone, followed by stereoselective trapping of the enolate generated from the resulting enol silyl ether with an allyl electrophile. Ring‐closing metathesis then establishes the 6–5 ring system. Likewise, selective preparation of the side chain features an enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Further simplification of acid 9 leads to intermediate 10 having the C 12 hydrocarbon and the highly oxidized fragment joined at a vinylic carbon of the hydrophobic fragment. 6 On the basis of our recent experience showing that fragment couplings of nucleophilic tertiary radicals with alkenes can be high yielding, 5b we envisioned a cascade sequence in which trisubstituted carbon radical B , generated by visible-light photoredox fragmentation of the N -acyloxyphthalimide substituent of intermediate 12 , 7 would couple with ( R )-4-methoxybutenolide ( 11 ) 8 to generate α-acyloxy-radical intermediate A , which was hoped would undergo intramolecular 5- exo cyclization from a conformation such as A ′ depicted in Scheme 1 that minimizes destabilizing allylic A 1,3 interactions. The cascade would then be terminated by β-fragmentation of the adjacent C–X (X = halide) bond to deliver the desired coupled product 10 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Further simplification of acid 9 leads to intermediate 10 having the C 12 hydrocarbon and the highly oxidized fragment joined at a vinylic carbon of the hydrophobic fragment. 6 On the basis of our recent experience showing that fragment couplings of nucleophilic tertiary radicals with alkenes can be high yielding, 5b we envisioned a cascade sequence in which trisubstituted carbon radical B , generated by visible-light photoredox fragmentation of the N -acyloxyphthalimide substituent of intermediate 12 , 7 would couple with ( R )-4-methoxybutenolide ( 11 ) 8 to generate α-acyloxy-radical intermediate A , which was hoped would undergo intramolecular 5- exo cyclization from a conformation such as A ′ depicted in Scheme 1 that minimizes destabilizing allylic A 1,3 interactions. The cascade would then be terminated by β-fragmentation of the adjacent C–X (X = halide) bond to deliver the desired coupled product 10 .…”
mentioning
confidence: 99%
“…11 In an exploratory model study, we confirmed that radical coupling at such a carbon would preferentially occur from the desired face syn to the vicinal substituent. 12 Further simplification of intermediate 12 leads to two readily available precursors: ( S , S )-trimethylhydrindanone 13 3 and ( R , R )-tartaric acid-derived acetonide 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a sequential ring closing metathesis followed by Heck coupling was shown in 2010, giving a trans-hydrindane core for the C/D ring juncture [78]. This methodology has been applied to the synthesis of norrisolide [79]. Metathesis as a cyclization tactic has become a notable method for ring forming reactions.…”
Section: Cyclization Strategies To Hydrindane Coresmentioning
confidence: 99%
“…Further, a sequential ring closing metathesis followed by Heck coupling was shown in 2010, giving a trans-hydrindane core for the C/D ring juncture [78]. This methodology has been applied to the synthesis of norrisolide [79]. Enyne metathesis has found an increasing interest in the synthesis of natural products (see Scheme 24) [80][81][82][83][84].…”
Section: Cyclization Strategies To Hydrindane Coresmentioning
confidence: 99%